The Water of Life: A Symbolic Journey from Epic to Mysticism and Lyricism - Alizade, Aygun (Rocznik Orientalistyczny/Yearbook of Oriental Studies, 2026)
The concept of the Water of Life is commonly encountered in folklore, epic and lyrical literature, as well as in Sufi literature. Each individual who refers to the Water of Life presents it in different meanings. Poets employ the Water of Life in the same context in which they perceive human beings’ attainment of eternal life. Some view it as being achieved through knowledge, others through wisdom, and others again through love, among other things. The approach each author takes toward the concept of the Water of Life is also varied. This paper explores the tale of Alexander’s search for the Water of Life, as depicted in Shāhnāmeh by Ferdowsī and Sharafnāmeh by Niẓāmī, and how it later entered Sufi literature, taking on a symbolic meaning. In medieval Persian literature, it is impossible to find a work that does not reference the Water of Life at least once. In the works of ʿAṭṭār, Rūmī, Hāfeẓ, Fużūlī, and many other great poets, various versions of this expression can be found. In this article, we attempt to examine the narrative of the Water of Life as it transitions from epic poetry to Sufi prose, specifically in the works of Avicenna and Suhrawardī.